Developing interactive e-module based on realistic mathematics education approach and mathematical literacy ability - Enggar Tri Aulia; Rully Charitas Indra Prahmana (Universitas Hamzanwadi, 2022)
Teaching and learning activities are carried out online during the pandemic situation. This condition makes the teaching and learning process in the classroom requires teaching materials that can support the learning process. However, some teachers still use teaching materials commonly used during face-to-face learning, which is irrelevant for offline learning. Therefore, teachers need alternative interactive teaching materials that can facilitate online learning. This study aims to produce teaching materials in an interactive e-module based on the Realistic Mathematics Education (RME) approach with the content of number pattern that is valid, practical, and have potentially affected the eight-grade students' mathematical literacy skills. The research method used is design research with type of development studies which include two main stages, namely the preliminary design and the formative evaluation. The data collection instruments used were content and media expert validation sheets, student response questionnaires, and pretest and posttest questions to measure mathematical literacy skills. This research produces an RME-based e-module on number pattern material that is valid, practical, and potentially affects mathematical literacy skills. The results showed that the e-module was valid in content and media quality with very good criteria. Next, the e-module has also been practical from assessing student responses with good criteria. Finally, the e-module can potentially improve students' mathematical literacy skills, which is indicated by the increase in students' mathematical literacy skills after learning to use the e-module. In addition, the e-module developed in this study contributes as alternative teaching material for teachers in the online learning system.